Branding Wooden Multi-storey Construction : Real-Estate Agents as Gatekeepers for Enhancing Consumer Value in Housing - Lähtinen, Katja; Häyrinen, Liina; Jussila, Jaakko; Harju, Charlotta; Toppinen, Anne; Toivonen, Ritva (Elsevier, 2022)
Understanding of consumer value expectations in the Finnish multistorey construction (MSC) markets is limited. Even less information exists on branding in the MSC businesses. Real-estate agents are powerful actors in the housing markets through their intermediary role between construction sector businesses and home purchasers. Despite this, their perceptions on the consumer value expectations or branding possibilities in the MSC markets has not been previously addressed. In our pilot study, by employing data gathered from real-estate agents from Finland in 2018 (n = 65, response rate 14%) we address the following questions: Based on real-estate agents’ perceptions, what are the housing value expectations of consumers in the Finnish multi-storey housing markets? Are there branding possibilities in those markets? Could wood be a source for branding in the MSC businesses? The quantitative and qualitative analysis show that branding opportunities exist. However, branding requires enhancing differentiation above traditional product-service thinking, which currently dominates MSC businesses.
Keywords: Binary logistic regression; Business ecosystems; Consumer choices; Differentiation; Housing expectations; marketing; fi=Markkinointi|en=Marketing|